Implementation of Mobile Based Virtual Reality on the Knights and Garuda Birds Folklore in the Legend of Mount Mekongga at Grade 7 of SMP Negeri 2 Kendari - Tahir, Arifin; Tahir, Muhlis; Takasi, La Ode Muhammad Ruspan; Arifrahman, Alif Adillah Nugraha (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Indonesia is a country rich in cultural values passed down from generation to generation, such as folklore. This challenge is be-cause folklore in Indonesia is told orally and mostly only docu-mented in the form of story books. So that folklore can be re-interested by children and to achieve the objectives of the learning process, visualizations are made using Virtual Reality technology. The folklore that will be raised is a folk tale from the province of Southeast Sulawesi entitled About the Knights and the Garuda Bird in the Legend of the Formation of Mount Mekongga. The purpose of this research is to be able to maintain folklore as a national cul-ture in the midst of the development of fictional stories by utilizing Virtual Reality technology. By using 2D moving image visualization and using Virtual Reality technology with the Sprint Model, it is hoped that students will be more interested in knowing folklore. There is an effect of learning models using Virtual on students on folklore material in class VII at SMPN 2 Kendari based on the gain test results that get a value of 0.6093, meaning that the learning outcomes before getting treatment with already getting treatment have increased by 0.6093. Student responses to questionnaires from student answers obtained a percentage of 85.5%, student responses after the learning process can be included in the "Very Strong" category. So, it can be concluded that the learning process by applying Virtual Reality gets a good response from all students.